Utilizing Caenorhabditis Elegans as a Rapid and Precise Model for Assessing Amphetamine‐Type Stimulants: A Novel Approach to Evaluating New Psychoactive Substances Activity and Mechanisms - Yuanpeng Li; Hongyuan Li; Hongshuang Wang; Xiaohui Wang (Advanced Science)
Abstract The surge of new psychoactive substances (NPS) poses significant public health challenges due to their unregulated status and diverse effects. However, existing in vivo models for evaluating their activities are limited. To address this gap, this study utilizes the model organism Caenorhabditis elegans (C. elegans) to evaluate the activity of amphetamine‐type stimulants (ATS) and their analogs. The swimming‐induced paralysis (SWIP) assay is employed to measure the acute responses of C. elegans to various ATS, including amphetamine (AMPH), methamphetamine (METH), 3,4‐methylenedioxymethamphetamine (MDMA) and their enantiomers. The findings reveal distinct responses in wild‐type and mutant C. elegans, highlighting the roles of dopaminergic and serotonergic pathways, particularly DOP‐3 and SER‐4 receptors. The assay also revealed that C. elegans can distinguish between the chiral forms of ATS. Additionally, structural activity relationships (SAR) are observed, with meta‐R amphetamines showing more pronounced effects than ortho‐R and para‐R analogs. This study demonstrates the utility of C. elegans in rapidly assessing ATS activity and toxicity, providing a cost‐effective and precise method for high‐throughput testing of NPS. These results contribute to a better understanding of ATS pharmacology and offer a valuable framework for future research and potential regulatory applications.